(untitled) (Economics and region, 2025)
The article examines the impact of the digitalisation of marketing activities on the economic security of enterprises in the digital economy. The key aspects of implementing marketing innovations, including digital technologies that change traditional approaches to marketing activities, are considered. The use of Big Data and analytics, automation of marketing processes, social media, artificial intelligence, personalised marketing communications and interactive tools such as virtual and augmented reality (VR/AR) are explored. The role of marketing innovations in shaping competitive advantages, increasing the effectiveness of communication with consumers and optimising costs for enterprises is defined. The author highlights the main risks of digital marketing, including cyber threats, personal data leaks, information manipulation, reputational risks, greenwashing, and dependence on digital platform policies, regulatory uncertainties, e-commerce fraud, and violation of ethical advertising standards. The article examines methods of managing these risks, in particular through implementing cybersecurity systems, using blockchain technologies for transparency of marketing operations, compliance with GDPR standards, applying ethical principles in digital advertising, and the improvement of legal literacy of enterprises. The article analyses the legal and regulatory framework for digital marketing activities in Ukraine, in particular, the provisions of the Laws of Ukraine: "On Personal Data Protection (No. 2297-VI); On Electronic Commerce (No. 675-VIII); On Digital Content and Digital Services (No. 3321-IX); On Advertising (No. 270/96-ВР); On Consumer Protection (No. 1023-XII); On Electronic Communications (No. 1089-IX); On Copyright and Related Rights (No. 2811-IX). As well as the International General Data Protection Regulation (GDPR). The problems of harmonisation of Ukrainian legislation with international standards and the need to improve the regulatory framework in the field of digital marketing are identified. The importance of an integrated approach to managing the risks of digitalisation of marketing, including measures of information protection, legal regulation and ethical standards of interaction with consumers, is substantiated.